Clinical Outcomes of PCI in patients with Multivessel CAD - Abdul Basit, Shahbaz Ali Shaikh, Roomana Khawaja Khail, Syed Kashif ur Rehman, Aziz Ullah, Hafsa (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the clinical outcomes of percutaneous coronary intervention in patients with multivessel coronary artery disease at a tertiary care hospital in Peshawar. Methodology: This retrospective descriptive study was conducted in the Department of Cardiology, tertiary care hospital, Peshawar, from June 2022 to May 2023. A total of 130 patients with multivessel coronary artery disease who underwent PCI were included through non-probability consecutive sampling. Data were collected from hospital records and analysed using SPSS version 26. Frequencies, percentages, mean and standard deviation were calculated. Chi-square test and independent sample t-test were applied, and a p-value of less than 0.05 was considered significant. Results: Among 130 patients, 86(66.2%) were male and 44(33.8%) were female. The mean age was 59.35±9.64 years. Major adverse cardiac events occurred in 31(23.8%) patients. In-hospital death was recorded in 7(5.4%) patients, post-PCI myocardial infarction in 10(7.7%), stroke in 5(3.8%), repeat revascularisation in 12(9.2%), stent thrombosis in 4(3.1%), bleeding in 8(6.2%), contrast induced nephropathy in 15(11.5%) and heart failure after PCI in 13(10.0%). PCI strategy was not significantly associated with MACE (p=0.150), while contrast induced nephropathy (p=0.033), higher contrast volume (p=0.001) and higher heart rate (p=0.044) were significantly linked with worse outcomes. Conclusion: PCI showed acceptable outcomes in multivessel coronary artery disease, but MACE remained clinically important. Renal protection, contrast reduction and close follow-up should be prioritised. Keywords: Percutaneous Coronary Intervention, Coronary Artery Disease, Multivessel Coronary Disease, Major Adverse Cardiac Events, Contrast Media.